Blurring boundaries of expert knowledge and stakeholder agenda - News media as a knowledge broker in the Finnish alcohol policy debate - Olli Seuri; Anu Katainen; Pihla Toivanen (Elsevier, 2023)
The news media are central to discussion on public policy as journalists regulate the flow and exchange of policy-relevant knowledge. In this article, we concentrated on the media's role as a knowledge broker, giving voice to and operating between different policy actors during the 2018 Alcohol Act reform in Finland. Particular attention was given to the way the alcohol industry stakeholders were positioned as information sources in the news reporting concerned with the evidence base for alcohol policy. Our study of four Finnish news media outlets shows how especially politicians and alcohol industry stakeholders are given voice in the news media. In addition, we identified three different ways in which the boundaries between commercial interests and research expertise were blurred. We argue that the news media blur these boundaries through what we call penetration, assimilation, and juxtaposition, and further that these ways of positioning stakeholders are embedded in the way news media handles conflicting evidence, presents facts, and quotes different sources without evaluating them. Using the reporting from alcohol policy debates as an example, we argue that the position of news media as a knowledge broker is vulnerable to stakeholder influence.